PERANAN DESA ADAT DALAM MELINDUNGI AIR TERJUN PENGEMPU DESA CAU BELAYU, TABANAN - Hendra Wijaya, I Made; Sutrisni, Ni Komang (Institut Hindu Dharma Negeri Denpasar, 2018)
In a study carried out in the area of Pengempu Waterfall, located in Cau Belayu Village, Tabanan Regency, to understand more about the role of traditional villages in maintaining the existence of the Pengempu waterfall. In this study using swot analysis to get how the benefits, impacts, disadvantages and benefits of the existence of this Pengempu waterfall to the community and how the participation of the village in protecting the area. The purpose of this study can provide awareness and strength and role of traditional villages in seeing the potential of their region and safeguarding their territory from the negative impacts of regional development.